Acute Toxicity Test of Shallot (Allium cepa L.) Peel Extract on Ovarian Follicles Count in Rats (Rattus norvegicus) - Dina Helianti (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2025)
Shallot skin (Allium cepa L.) is a natural material with potential as a traditional medicine due to its high content of the antioxidant quercetin. However, excessive consumption of shallot skin may cause the antioxidant properties of quercetin to shift to pro-oxidant effects via auto-oxidation and metal-binding reactions. Uncontrolled pro-oxidants induce oxidative stress that damages body cells, including ovarian follicle cells. This acute toxicity study aimed to evaluate the toxic effects of shallot skin extract on the ovary using ovarian follicle count as an indicator. This study employed a true experimental design with a posttest-only control group. The method referred to the OECD 420 guideline (fixed dose procedure) using rats (Rattus norvegicus) as test animals. The results showed no significant difference in the mean follicle counts between the control and treatment groups across all follicle categories: primary follicles (p = 0.278), secondary follicles (p = 0.452), DeGraaf follicles (p = 0.39), corpus luteum (p = 0.752), atretic follicles (p = 1.0), and total follicles (p = 0.60). Thus, follicle counts in all categories did not differ significantly (p>0.05). It can be concluded that shallot skin extract does not exert toxic effects on ovarian follicle numbers in rats.